The Comparison of the Surgical Outcome for the Full-Thickness Macular Hole with/without Lamellar Hole-Associated Epiretinal Proliferation. (13th December 2017) - Ubukata, Yuri; Imai, Hisanori; Otsuka, Keiko; Nishizaki, Masaya; Hara, Rumiko; Uenishi, Mamoru; Azumi, Atsushi; Nakamura, Makoto
Abstract : Aims . To compare the surgical outcome of pars plana vitrectomy (PPV) for full-thickness macular hole (FTMH) with and without lamellar hole-associated epiretinal proliferation (LHEP). Methods . This retrospective study included 158 eyes of 158 patients with FTMH treated with PPV. The following variables were analyzed: sex, age, preoperative best corrected visual acuity (pre-BCVA), BCVA 6 months after the surgery (6M-BCVA), the axial length of eye, the minimum diameter of FTMH, the diameter of basal side of FTMH, postoperative continuity of subfoveal ellipsoid zone (EZ) and external limiting membrane (ELM), and the preoperative presence of LHEP. Results . Twenty-eight eyes had FTMH with LHEP and 130 without LHEP. The mean ± SD age (years) was 72.6 ± 7.9 and 68.6 ± 8.7, respectively (p = 0.02 ). 6M-BCVA was 0.38 ± 0.30 and 0.26 ± 0.25, respectively (p = 0.03 ). The diameter of basal side of FTMH ( μ m) was 901.5 ± 404.9 and 658.9 ± 288.1, respectively (p = 0.00027 ). EZ was disrupted in 24 eyes and 63 eyes, respectively (p = 0.00071 ). ELM was disrupted in 15 eyes and 23 eyes, respectively (p = 0.00015 ). The FTMH diameters and the presence of LHEP were inversely correlated with the continuity of EZ and ELM. Conclusion . The preoperative appearance of LHEP could be one of the prognostic factor for the treatment of FTMH.